2015
DOI: 10.1128/jcm.03094-14
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry Meropenem Hydrolysis Assay with NH 4 HCO 3 , a Reliable Tool for Direct Detection of Carbapenemase Activity

Abstract: A comparison of a matrix-assisted laser desorption ionization-time of flight mass spectrometric (MALDI-TOF MS) meropenem hydrolysis assay with the Carba NP test showed that both methods exhibited low sensitivity (approximately 76%), mainly due to the false-negative results obtained with OXA-48-type producers. The addition of NH 4 HCO 3 to the reaction buffer for the MALDI-TOF MS assay dramatically improved its sensitivity (98%). Automatic interpretation of the MALDI-TOF MS assay, using the MBT STAR-BL software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 36 publications
3
78
0
1
Order By: Relevance
“…Like the Carba NP test, MALDI-TOF assays have reported difficulty detecting OXA-48-like enzymes. One study reported a sensitivity of 77% and a specificity of 100%, with the lower sensitivity being due to missing 16 of 19 OXA-48 producers (24). However, this report suggested that the MALDI-TOF carbapenemase assay could be modified (by the addition of bicarbonate) to improve its performance for the OXA-48 producers with little impact on detection of other enzymes (sensitivity improved to 98%) (24).…”
Section: Phenotypic Cp-cre Detection Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…Like the Carba NP test, MALDI-TOF assays have reported difficulty detecting OXA-48-like enzymes. One study reported a sensitivity of 77% and a specificity of 100%, with the lower sensitivity being due to missing 16 of 19 OXA-48 producers (24). However, this report suggested that the MALDI-TOF carbapenemase assay could be modified (by the addition of bicarbonate) to improve its performance for the OXA-48 producers with little impact on detection of other enzymes (sensitivity improved to 98%) (24).…”
Section: Phenotypic Cp-cre Detection Methodsmentioning
confidence: 98%
“…Imipenem hydrolysis changes the pH and produces a resultant color change of a pH indicator. The Carba NP is faster than the MHT described above and has excellent sensitivity for most carbapenemases (reported range, 73 to 100%) (18,23,24,25). Its sensitivity for the OXA-48 carbapenemase is much lower; only 1 of 17 OXA-48 producers was detected in one study (24).…”
Section: Phenotypic Cp-cre Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations